Prescription trajectories and effect of total hip arthroplasty on the use of analgesics, hypnotics, antidepressants, and anxiolytics: results from a population of total hip arthroplasty patients. Issue 3 (March 2016) - Blågestad, Tone; Nordhus, Inger H.; Grønli, Janne; Engesæter, Lars B.; Ruths, Sabine; Ranhoff, Anette H.; Bjorvatn, Bjørn; Pallesen, Ståle
Abstract : Abstract: Total hip arthroplasty (THA) has been shown to reduce pain and improve function. In addition, it is suggested that THA improves sleep and alleviates symptoms of anxiety and depression. Patients with chronic pain are frequent users of analgesic and psychotropic drugs and thereby risk adverse drug events. The impact of THA on such drug use has not been thoroughly investigated. Based on merged data from the Norwegian Prescription Database and the Norwegian Arthroplasty Register, this study sought to investigate redeemed medications in a complete population (N = 39, 688) undergoing THA in 2005 to 2011. User rates and redeemed drug volume of analgesics (nonsteroid anti-inflammatory drugs (NSAIDs), opioids, and nonopioids) and psychotropics (hypnotics, anxiolytics, and antidepressants) were calculated for 4 quarters before and 4 quarters after surgery. We analysed preoperative prescription trends (Q1 vs Q4), postoperative prescription (Q4 vs Q5), and long-term effect of surgery (Q4 vs Q8). Before surgery, use of all drug groups increased from Q1 to Q4. Use of opioids, nonopioids, and hypnotics dramatically increased from Q4 to Q5. Long-term (Q4 vs Q8) surgery reduced prescriptions of analgesics, hypnotics, and anxiolytics, but not antidepressants. Overall, the present results extend the positive effects of THA to include reduced reliance on medication to alleviate symptoms. Abstract : Total Hip Arthroplasty reduces prescription use of analgesics, hypnotics, and anxiolytics and prescription trajectories follow clinical pain trajectories for analgesics and hypnotics before and after surgery.